Anesthetic management for a cesarean section in a parturient with huge vulvar and lower limbs elephantiasis: a case report - Sethi, Surendra Kumar; Jain, Kavita; Jain, Neena; Yadav, Sohan Lal (Journal of Society of Anesthesiologists of Nepal, 2018)
Elephantiasis is caused by accumulation of lymph in soft tissues due to long standing lymphatic obstruction. Elephantiasis of female external genitalia is very rare and its association with limb elephantiasis is also quite very rare. A 20 years old, primigravida patient with 38 weeks’ gestation presented with massive swelling of lower limbs along with vulvar edema posted for emergency cesarean section diagnosed as elephantiasis of lower limbs and vulva which is usually rare and has not been reported yet. Elephantiasis in pregnancy poses difficulty for an anesthesiologist while providing neuraxial anesthesia to such a patient. We report the anesthetic management of a primigravida patient with both vulvar and lower limbs elephantiasis posted for emergency cesarean section. Journal of Society of Anesthesiologists of Nepal Vol. 4, No. 2, 2017, Page: 91-93